Articles - Jean Demangeot (Cahiers de géographie du Québec, 2005)
Where the Great Whale River empties into the Hudson Bay, it is intrenched in the Tyrrel Sea sands (altitude : about 30 m) and in slightly older glacio-marine clays. On the left side of the river, this materials is eaten away by a dozen hemicycles. This morphology has been produced, during the last two milleniums by the succession of five different processes : 1) slow solifluxion, 2) thermokarstic subsidence, 3) nival sheet-wash, 4) sudden flowage, in the presence of concave faults, 5) gentle mud flowing. Certainly nivation has been as important a factor as the melting of permafrost in this nophogenesis. À son débouché dans la mer d'Hudson, la Grande rivière de la Baleine s'encaisse dans les sables de la mer de Tyrrel (altitude : une trentaine de mètres), puis dans des argiles glacio-marines plus anciennes. Or, sur la rive gauche, une douzaine d'hémicycles mordent dans ce matériel argilo-sableux. Ils sont dus à des glissements de terrain, provoqués par la succession de cinq processus différents au cours des deux derniers millénaires : 1) gélifluxion lente, 2) affaissement thermokarstique, 3) ruissellement laminaire, 4) brusque foirage avec failles courbes, 5) petit écoulement boueux. La nivation a certainement joué un rôle aussi important que la fusion du permafrost dans le façonnement de ces hémicycles.